Rethinking the concept of autonomy for the sociology of symbolic goods (Práxis Educativa, 2020)
What is meant by “autonomy” in the human and social sciences? The concept’s multiple meanings make it susceptible to mishandling. These meanings refer to distinct traditions, from the theme of political autonomy, which can be traced back to autonomy in Ancient Greek cities, to that of individual autonomy, a concern that grew along with the development of the Protestant ethic and humanist thought, as theorized in Kant’s ‘autonomy of reason.’ Autonomy also holds a place of choice in sociological reflections on the conditions of production and circulation of symbolic goods, which will be the focus of this paper: it is used to analyse the relationship between these goods and economic, social, and political conditions, without reducing goods to conditions. However, here too, meanings vary between the three strands of research that have systematically used and discussed it 2 since the 1950-1960s: the sociology of professions, Marxist reflection theory, and field theory (1). Despite these differentiated, partly incompatible uses, there are overlap areas and possible bridges to cross between these approaches (2). They suggest proposals for a reasoned synthesis of these uses in sociological analysis of the production and circulation of symbolic goods (3).Keywords: Sociology of symbolic goods. Concept of autonomy. Sociology of professions. Marxist reflection theory. Field theory.